The Relationship Between Metacognition and Vocational Indecision - Symes, Brent A.; Stewart, John B. (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this study was to examine the relationship between metacognition and vocational indecision among 100 introductory Psychology students within the parameters of the theory of cognitive information processing advanced by Peterson, Sampson, Reardon and Lenz (1996). The Cornell Critical Thinking Test was employed as a measure of metacognition and the Career Decision Scale served as the measure of vocational indecision. The results of a correlation analysis revealed a significant statistical relationship between metacognition and vocational indecision. In particular, individuals who scored higher on the measure of metacognition, indicating increased metacognitive activity such as monitoring and regulation, evidenced a greater degree of vocational decidedness. Alternatively, those who scored lower were found to be more vocationally undecided. Regression analysis revealed deduction, one of the components of metacognition, as a predominant predictor for decidedness.